A new species of Zygophylax (Quelch, 1885) (Cnidaria, Hydrozoa) from South Africa, with taxonomic notes on the southern African species of the genus - Campos, Felipe Ferreira; Pérez, Carlos Daniel; Puce, Stefania; Marques, Antonio Carlos (Zootaxa, 2020)
The genus Zygophylax is a genus of leptothecate hydroids considerably rich in the number of species in the deep sea. In this study we review five species, Z. africana, Z. crozetensis, Z. infundibulum, Z. millardae and Z. geminocarpa, from southern Africa based on available material from several collections, describing and illustrating materials from type series or additional material. Additionally, we describe Zygophylax naomiae sp. nov. collected in South Africa at a depth of 287 m, distinguished from its congeners by the strong pattern of annulations of the pedicels of the hydrotheca and the nematotheca.